2020
DOI: 10.1186/s12935-020-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related gene signature for predicting the prognosis of head and neck squamous cell carcinoma

Abstract: Background: Immune-related genes (IRGs) were linked to the prognosis of head and neck squamous cell carcinoma (HNSCC). This study aimed to identify the effects of an immune-related gene signature (IRGS) that can predict the of HNSCC prognosis. Methods: The expression data of 770 HNSCC patients from the TCGA database and the GEO database were used. To explore a predictive model, the Cox proportional hazards model was applied. The Kaplan-Meier survival analysis, as well as univariate and multivariate analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…In the present study, we developed a prognostic signature based on 10 immune-related genes from TCGA datasets and validated them using GEO datasets. The patients in the high risk group were considered to have short survival times in both datasets, in accordance with previous studies [15]. ROC analysis indicated that our immune signature exhibited better sensitivity and specificity for survival prediction at 2-, 3-and 5-years, even exceeding the predictive ability of TNM stage.…”
Section: Genetic Alterations and Gsea Analysis In The High-risk Groupssupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, we developed a prognostic signature based on 10 immune-related genes from TCGA datasets and validated them using GEO datasets. The patients in the high risk group were considered to have short survival times in both datasets, in accordance with previous studies [15]. ROC analysis indicated that our immune signature exhibited better sensitivity and specificity for survival prediction at 2-, 3-and 5-years, even exceeding the predictive ability of TNM stage.…”
Section: Genetic Alterations and Gsea Analysis In The High-risk Groupssupporting
confidence: 84%
“…Checkpoint blockade immunotherapeutics, such as nivolumab and pembrolizumab, are primarily used in the patients with recurrent or metastatic disease, but the observed objective response rates are in the range of only 16-25% [12,13]. Increasing evidence has also revealed that a prognostic signature containing several to dozens of genes have laid a foundation for predicting the survival of HNSCC [14][15][16]. To our knowledge, there is no immune-related prognostic signature which can not only predict survival, but may be associated with the immune checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-in ltrating immune cells played a key function in the genesis and progress of tumors [21]. Therefore, the potential association between risk score and level of immune in ltration in the whole TCGA set was analyzed.…”
Section: Clinical Utility Of the Prognostic Risk Model In The Whole Tmentioning
confidence: 99%
“…By acting on the immune checkpoints, it has been used to treat a variety of cancers, including sarcoma [15]. More importantly, previous studies indicated that immune-related genes(IRGs) can serve as an effective prognostic biomarkers in many tumors, such as lung cancer [16][17][18][19], ovarian cancer [20,21], hepatocellular carcinoma [22,23], head and neck squamous cell carcinoma [24], papillary thyroid cancer [25], bladder urothelial carcinoma [26], and renal cancer [27]. Nonetheless, the prognostic signi cance of IRGs in sarcoma remains unclear but urgent.…”
Section: Introductionmentioning
confidence: 99%